Periodontal pockets: predictors for site-related worsening after non-surgical therapy: a long-term retrospective cohort study - Herz, Marco Michael; Hoffmann, Nina; Braun, Sandra; Lachmann, Stefan; Bartha, Valentin; Petsos, Hari (Journal of clinical periodontology, 2024)
Aim: To evaluate site-related changes in periodontal pocket depth (PPD) after non-surgical periodontal therapy and to identify predictors for PPD changes in a retrospective patient data analysis. Materials and Methods: PPD, clinical attachment level, bleeding on probing, tooth mobility (TM), furcation involvement (FI), abutment status, adherence to supportive periodontal care (SPC) and SPC follow-ups were obtained from fully documented patient data before periodontal therapy (baseline, T0), after active periodontal therapy (APT, T1) and during SPC (T2). PPD changes were classified into deteriorated or unchanged/improved at the site level. Multi-level logistic regression analysis was performed to identify factors influencing PPD changes during SPC. Results: This retrospective study included 51 females and 65 males (mean T0 age: 54.8 ± 10.1 years, 25 smokers, 12 diabetics) suffering from Stage III/IV periodontitis. Evaluation outcome: T0/16,044 sampling sites/2674 teeth; T1/15,636/2606; T2/14,754/2459. During 9.0 ± 2.3 years SPC, PPD decreased (−1.33 ± 0.70 mm) by 21.8% of the sites, remained unchanged by 41.4% and increased (1.40 ± 0.78 mm) by 36.8%. Distopalatal FI (p < .001, odds ratio [OR]: 0.252, 95% confidence interval [CI] for OR: 0.118-0.540), residual pockets (p < .001, OR: 0.503, 95% CI: 0.429-0.590) and TM Degrees I-III (Degree I: p = .002, OR: 0.765, 95% CI: 0.646-0.905; Degree II: p = .006, OR: 0.658, 95% CI: 0.489-0.886; Degree III: p = .023, OR: 0.398, 95% CI: 0.180-0.879) correlated significantly with increasing PPD. Conclusions: Over 75% of PPD remained unchanged or increased during SPC. Distopalatal FI, TM Degrees I-III and residual pockets after APT lead to worsening of periodontal pockets.
Gesehen am 23.07.2024
Erstveröffentlichung: 22. Februar 2024